Identification of Novel Causal FBN1 Mutations in Pedigrees of Marfan Syndrome - Yueli Wang; Xiaoyan Li; Rongjuan Li; Ya Yang; Jie Du (International Journal of Genomics)
Marfan syndrome (MFS) is an autosomal dominant genetic disorder of the connective tissue, typically characteristic of cardiovascular manifestations, valve prolapse, left ventricle enlargement, and cardiac failure. Fibrillin-1 (FBN1) is the causative gene in the pathogenesis of MFS. Patients with different FBN1 mutations often present more considerable phenotypic variation. In the present study, three affected MFS pedigrees were collected for genetic analysis. Using next-generation sequencing (NGS) technologies, 3 novel frameshift pathogenic mutations which are cosegregated with affected subjects in 3 pedigrees were identified. These novel mutations provide important diagnostic and therapeutic insights for precision medicine in MFS, especially regarding the lethal cardiovascular events.